Nuzul yat Muhkamat. Methodology Based on the History of Maqbul in the Perspective of Ta'addud Asbab al-Nuzul - Wisudaningsih, Endah Tri; Safari, Moch. Umar (Eximia, 2022)
Al-Qur'an is the last holy book which must be kept from disfigurement, not only the texts but also the meaning. Many Islamic theologians have devoted all of their abilities in producing many rules of Islam which've been taken with deep-knowladges. In the midst of Islamic knowledge which must be mastered in understanding the Qur'an are asbabun nuzul and muhkam-mutasyabih. The concept of asbabun nuzul requires knowledge of hadith transmissions. On hadith asbabun nuzul transmissions can be found on many literatures of Islamic books which're written by Islamic theologians. This research is used to analyze all of the hadith asbabun nuzul transmissions through can be gathered hadith asbabun nuzul which're accepted or maqbul. As usual pattern on hadith, accepted-hadith transmissions are devided to hadith shahih and hasan. The accepted-hadith transmissions is necessary to determine the exact descent of clauses Qur'an either place background or time background. The hadith asbabun nuzul transmissions are classified depending on its variety of asbabun nuzul. The variety of asbabun nuzul consists of one cause to some clauses of the Qur'an and some causes to one clause of the Qur'an. The muhkam clauses which have accepted-hadith transmissions are used to deliver some laws of the Qur'an by Islamic theologians. The methodology of determining descent of muhkam clauses can be determined with elaborating the literature of asbabun nuzul and the interpretation book of muhkam clauses. In order to realize it, this research uses two main references. These are al-Shahih al-Musnad min Asbab al-Nuzul which's written by Shaikh Abu Abdurrahman Muqbil bin Hadi al-Wa'di'i and Asbab al-Nuzul by Abu al-Hasan 'Ali bin Ahmad al-Wahidi al-Naysaburi and Al-Jami' li-Ahkami al-Qur'an which's written by Shaikh Muhammad bin Ahmad Ab Bakr bin Farh al-Anshari al-Andalusi al-Qurtubi. In order to realize it, this research uses two main references. These are al-Shahih al-Musnad min Asbab al-Nuzul which's written by Shaikh Abu Abdurrahman Muqbil bin Hadi al-Wa'di'i and Asbab al-Nuzul by Abu al-Hasan 'Ali bin Ahmad al-Wahidi al-Naysaburi and Al-Jami' li-Ahkami al-Qur'an which's written by Shaikh Muhammad bin Ahmad Ab Bakr bin Farh al-Anshari al-Andalusi al-Qurtubi. In order to realize it, this research uses two main references. These are al-Shahih al-Musnad min Asbab al-Nuzul which's written by Shaikh Abu Abdurrahman Muqbil bin Hadi al-Wa'di'i and Asbab al-Nuzul by Abu al-Hasan 'Ali bin Ahmad al-Wahidi al-Naysaburi and Al-Jami' li-Ahkami al-Qur'an which's written by Shaikh Muhammad bin Ahmad Ab Bakr bin Farh al-Anshari al-Andalusi al-Qurtubi.